Influence of implant strategy on the transition from temporary left ventricular assist device to durable mechanical circulatory support - Meyer, Anna L.; Lewin, D; Billion, M; Hofmann, S; Netuka, I; Belohlavek, J; Jawad, K; Saeed, D; Schmack, B; Rojas, S V; Gummert, J; Bernhardt, A; et al. (European journal of cardio-thoracic surgery, 2024)
Bridging from a temporary microaxial left ventricular assist device (tLVAD) to a durable left ventricular assist device (dLVAD) is playing an increasing role in the treatment of terminally ill patients with heart failure. Scant data exist about the best implant strategy. The goal of this study was to analyse differences in the dLVAD implant technique and effects on patient outcomes.Data from 341 patients (19 European centres) who underwent a bridge-to-bridge implant from tLVAD to dLVAD between January 2017 and October 2022 were retrospectively analysed. The outcomes of the different implant techniques with the patient on cardiopulmonary bypass, extracorporeal life support or tLVAD were compared.A durable LVAD implant was performed employing cardiopulmonary bypass in 70% of cases (n = 238, group 1), extracorporeal life support in 11% (n = 38, group 2) and tLVAD in 19% (n = 65, group 3). Baseline characteristics showed no significant differences in age (P = 0.140), body mass index (P = 0.388), creatinine level (P = 0.659), the Model for End-Stage Liver Disease (MELD) score (P = 0.190) and rate of dialysis (P = 0.110). Group 3 had significantly fewer patients with preoperatively invasive ventilation and cardiopulmonary resuscitation before the tLVAD was implanted (P = 0.009 and P < 0.001 respectively). Concomitant procedures were performed more often in groups 1 and 2 compared to group 3 (24%, 37% and 5%, respectively, P < 0.001). The 30-day mortality data showed significantly better survival after an inverse probability of treatment weighting in group 3, but the 1-year mortality showed no significant differences among the groups (P = 0.012 and 0.581, respectively). Postoperative complications like the rate of right ventricular assist device (RVAD) implants or re-thoracotomy due to bleeding, postoperative respiratory failure and renal replacement therapy showed no significant differences among the groups. Freedom from the first adverse event like stroke, driveline infection or pump thrombosis during follow-up was not significantly different among the groups. Postoperative blood transfusions within 24 h were significantly higher in groups 1 and 2 compared to surgery on tLVAD support (P < 0.001 and P = 0.003, respectively).In our analysis, the transition from tLVAD to dLVAD without further circulatory support did not show a difference in postoperative long-term survival, but a better 30-day survival was reported. The implant using only tLVAD showed a reduction in postoperative transfusion rates, without increasing the risk of postoperative stroke or pump thrombosis. In this small cohort study, our data support the hypothesis that a dLVAD implant on a tLVAD is a safe and feasible technique in selected patients.